Health and Safety Risk Assessment Using a Combined FMEA and JSA Method in a Manufacturing Company - Jaddi Madarsara, Tayyebeh; Yari, Saeed; Saeidabadi, Hamzeh (Asian Pacific Journal of Environment and Cancer, 2019)
Background: Occupational accidents cause three to four times as many deaths in developing countries as industrialized countries. There are about 14,000 accidents in Iran every year, most of them involving workers in industries, To reduce these accidents, it is necessary to use risk assessment, which is a rational approach to hazard assessment and to identify hazards and potential consequences, on individuals, materials, equipment and the environment to reduce the risks of workplace accidents and consequently work-related accidents. Methods: This study was carried out in 1998 as an analytical-applied study in a manufacturing company. The Risk Assessment process, first with the formation of the relevant team, is selected from technical and production specialists who are more familiar with the concept of safety and risk assessment and again how to perform the Risk Assessment and Identify the risks involved, using the JSA Integrated Method for the analysis of business components and associated risks and FMEA method was trained and targeted to determine system failure states as well as assign risk priority number (RPN). Results: Risk assessment was carried out in 4 aspects, locations, equipment, main and sub-units and activities leading to the preparation of tables related to the risk assessment guide of locations, equipment, activities, RPN calculation, risk level classification and identification forms. Conclusions: In this study, 166 hazards were identified and, through follow-up and collaboration with senior management of the organization from 38 risks of fluids production hall, 22 corrective action (57.89%), from 46 risks of solids production hall, 37 corrective action (80.43%), from 33 risks of product warehouse, 28 corrective actions (84.84%), from 30 risks of raw materials warehouse, 21 corrective actions (70%), from 19 risk of incendiary materials, 10 corrective actions (52.63%) were performed. The overall results of the study showed that the major risk in the studied units was related to the dangers of inadequate cabling and placement of people in these work situations. key words: Safety and Health Risk Assessment, FMEA, JSA, AHA, JHA, THA, Executive Procedure, Guidelines.